Implementasi Pembelajaran Berbasis Inkuiri Wenning Berbantuan e-UKBM untuk Meningkatkan Keterampilan Ilmiah Peserta Didik - Emy Kertiasih, Luh (Universitas Pendidikan Ganesha, 2018)
Science is essentially about product (scientific knowledge) and process (scientific inquiry). Science product and process have an equally important position in learning. However, the learning process about science, especially Biology, in the classroom only aims to understand and implement the concept, principle, and biological law. This causes students' scientific skills to be low. One of efforts that can be done to improve scientific skills is by implementing inquiry-based learning assisted by e-UKBM. This study aims to improve the students’ scientific skills and to determine the response of students to the learning that is applied. The subjects in this study were 27 students in class XI IPA 2 in SMA Negeri Bali Mandara in the odd semester of Academic Year 2018/2019. Scientific skills in this study were measured using an observation sheet. Based on this research, it was found that the students’ scientific skills had exceeded minimal learning completeness. Therefore, this study had succeeded in improving the students’ scientific skills.